El cine documental mexicano hecho por mujeres - María del Carmen DE LARA RANGEL (Fonseca, Journal of Communication, 2023)
Cultural construction and women’s efforts in documentary films seem to be hidden by a patriarchal view. Women’s history in Mexican documentary films has been excluded by the lack of tolerance, and some of these women in Mexico have been rescued by one of the most dedicated women on cinematography topics: Patricia Torres San Martin.